Seismic performance improvement of low to mid rise gravity load designed reinforced concrete frame buildings by buckling restrained braces and fiber reinforced polymer - Phichaya Suwansaya; Pennung Warnitchai; Anwar, Naveed; Kyung- Ho Park; Sun Sayamipuk; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
In this study, the seismic performance of low to mid rise gravity load design reinforce concrete frame building are presented. Furthermore the seismic performance of this building after adding BRBs and FRPs are presented. The commercial building with 4 sto ries and first soft storey which is the typical building that can be found in Bangladesh is selected to use as original building to study. This building is evaluated the seismic performance with cyclic pushover analysis and 3D nonlinear dynamic time histor y analysis. Furthermore, the design of retrofitting techniques which are BRB and FRP are presented in purpose to optimize the effectiveness of retrofitting schemes. The comparisons of the predicted response and the analysis response are discussed to check the design procedure. Later on, the comparison of each retrofitting technique is compared in term of the seismic performance, construction time, disrupting building functionality and cost. Both BRB and FRP techniques can enhance the seismic performance of the original structure. As compared in term of seismic performance, building functionality, restoring time and cost, FRP seems to be a better technique to improve the seismic performance of low to mid rise GLD buildings.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2010
Keywords: Buildings, Reinforced concrete -- Earthquake effects